Standardized aseptic dressing change procedure: Optimizations and adherence in a prospective pre- and postintervention cohort study. (24th June 2022) - Neuwirth, Meike M.; Herbrandt, Swetlana; Mattner, Frauke; Otchwemah, Robin
Abstract: Background: The "HygArzt" project investigated the effectiveness of hygiene measures introduced by an infection prevention link physician (PLP). Objective: To investigate whether the introduction of a standardized aseptic dressing change concept (ADCC) by a PLP can increase hand hygiene adherence and adherence to specific process steps during an aseptic dressing change (ADC) in a trauma surgery and orthopedic department. Methods: We defined 4 required hand disinfection indications: (1) before the preparation of ADC equipment, (2) immediately before the ADC, (3) before the clean phase, and (4) after the ADC. A process analysis of the preintervention phase (331 ADCs) was used to develop a standardized ADCC. The ADCC was introduced and iteratively adopted during the intervention phase. The effect was evaluated during the postintervention phase (374 ADCs). Results: Hand hygiene adherence was significantly increased by the introduction of the ADCC for all indications: (1) before the preparation of the ADC equipment (from 34% before to 85% after, P <.001), (2) immediately before an ADC (from 32% before to 85% after; P < .001), (3) before the clean phase (from 42% before to 96% after; P < .001), and (4) after an ADC (from 74% before to 99% after; P < .001). Overall hand hygiene adherence was analyzed before the indications for an ADC (from 9.6% before to 74% after; P < .001). The same strategy was applied to the following process parameters: use of a clean work surface, clean withdrawal of equipment from the dressing trolley, and appropriate waste disposal. Conclusions: A PLP sufficiently implemented a standardized concept for aseptic dressing change during an iterative improvement process, which resulted in a significant improvement in hand hygiene and adherence to other specific ADCC process steps.